Transmission of SARS-CoV-2 in Public Transportation Vehicles: A Case Study in Hunan Province, China. (13th September 2020) - Luo, Kaiwei; Lei, Zhao; Hai, Zheng; Xiao, Shanliang; Rui, Jia; Yang, Hao; Jing, Xinping; Wang, Hui; Xie, Zhengshen; Luo, Ping; Li, Wanying; Li, Qiao; et al.
Abstract: Here we report a case study of a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak event during bus trips of an index patient in Hunan Province, China. This retrospective investigation suggests potential airborne transmission of SARS-CoV-2 and the possibility of superspreading events in certain close contact and closed space settings, which should be taken into account when control strategies are planned.